2022
DOI: 10.14739/2310-1210.2022.3.243836
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonitoring of Alternaria spores in the air of Zaporizhzhia city

Abstract: The aim of the study was to determine the patterns of changes in the concentration of mold spores of the genus Alternaria in the air of Zaporizhzhia city. Materials and methods. The object of the study was the dynamics of Alternaria spore concentration in the atmospheric air of Zaporizhzhia city. The study was carried out at the Department of Medical Biology, Parasitology and Genetics of Zaporizhzhia State Medical University. Samples were taken annually from March 1 to October 31 by volumetric method using a H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Long-term aerobiological monitoring in Europe and worldwide has shown that fungi of the genus Alternaria are widespread. According to reports from two air monitoring stations in Vinnytsia [1] and Zaporizhzhya [2], the fungus Alternaria is predominant in the air of Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term aerobiological monitoring in Europe and worldwide has shown that fungi of the genus Alternaria are widespread. According to reports from two air monitoring stations in Vinnytsia [1] and Zaporizhzhya [2], the fungus Alternaria is predominant in the air of Ukraine.…”
Section: Introductionmentioning
confidence: 99%